Climate change, power, and vulnerabilities in the Peruvian Highlands - Heikkinen, Anna (2023)
The intensifying impacts of climate change pose a serious global threat, particularly for rural populations whose livelihoods are closely tied to natural resources. Yet there is a lack of critical understanding of how asymmetric power dynamics shape the vulnerabilities of such populations under climate change. This article examines the interrelations between smallholders’ climate-related vulnerability experiences and power relations across multiple scales of climate adaptation in the Peruvian Andes, a region susceptible to increasing climatic threats. The analysis draws on a case study conducted in the Mantaro River Valley in Central Peru using qualitative methods: open-ended interviews, participant observation, and document analysis. Findings of the study show that in the context of climate change, the production of vulnerabilities has much to do with larger socio-political structures in which protection of the highland farmers is not prioritized. Their marginalization in climate adaptation and other overlapping fields of policy have created uneven terms of adaptation among smallholders. This has created further marginalization, conflicts, and deepened smallholders’ vulnerabilities under climate change. I argue that to reach a better understanding of the multidimensionality of vulnerabilities, more detailed attention must be paid to place-based climate experiences within context-specific, socio-political processes, and to the ways these are shaped by unequal power relations across multiple scales.